Release Kinetics of Hydroxypropyl Methylcellulose Governing Drug Release and Hydrodynamic Changes of Matrix Tablet - Park, Chulhun; Lee, Jong Hoon; Jin, Gang; Van Ngo, Hai; Park, Jun Bom; Tran, Thao T.D.; Tran, Phuong H.L.; Lee, Beom Jin (Current Drug Delivery, 2022)
Background: Hydrophilic Hydroxypropyl Methylcellulose (HPMC) matrix tablets are the standard role model of the oral controlled-release formulation. Nevertheless, the HPMC kinetics for the mechanistic understanding of drug release and hydrodynamic behaviors are rarely in-vestigated. This study aims to investigate the release behaviors of both HPMC and paracetamol (model drug) from the hydrophilic matrix tablet. Methods: Two different viscosity grades of HPMC were used (Low viscosity: 6 cps, High viscosi-ty: 4,000 cps). Three different ratios of drug/HPMC (H:38.08%, M:22.85%, and L:15.23% (w/w) of HPMC amounts in total weight) matrix tablets were prepared by wet granulation technique. The release profiles of the drug and HPMC in a matrix tablet were quantitatively analyzed by HPLC and1H-Nuclear Magnetic Resonance (NMR) spectroscopy. The hydrodynamic changes of HPMC were determined by the gravimetric behaviors such as swelling and erosion rates, gel layer thick-ness, front movement data,and distributive Near-Infrared (NIR) chemical imaging of HPMC in a matrix tablet during the dissolution process. Results: High viscosity HPMC tablets showed slower release of HPMC than the release rate of drug, suggesting that drug release preceded polymer release.Different hydration phenomenon was qualitatively identified and corresponded to the release profiles. The release behaviors of HPMC and drug in the tablet could be distinguished with the significant difference with fitted dissolution kinetics model (Low viscosity HPMC 6cps; Korsmeyer-Peppas model, High viscosity HPMC 4000cps; Hopfenberg model, Paracetamol; Weibull model) according to the weight of ingredients and types of HPMC. Conclusion: The determination of HPMC polymer release correlating with drug release, hydrodynamic behavior, and NIR chemical imaging of HPMC can provide new insights into the drug re-lease-modulating mechanism in the hydrophilic matrix system.
Keywords: Acetaminophen; Delayed-Action Preparations; Drug Liberation; Hydrodynamics; Hypromellose Derivatives; Kinetics; Methylcellulose; Polymers; Solubility; Tablets; Viscosity; distributive imaging of polymer; drug release; hydrodynamic behaviors; Hydroxypropyl methylcellulose; polymer release; quantitative and qualitative analysis of HPMC